Comparative Analysis Of The Central Business District (CBD) in Pangkalan Bun: Market Affected Areas Versus Governmental – Affected Areas Based on Gross Income Multiplier (GIM) and Government Assessed Property Value (NJOP) in The Surrounding Area - Priambodo, M. Fakhry; Isnanto, Isnanto (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
Pangkalan Bun, the capital of West Kotawaringin Regency, is shaped by two primary urban centers that significantly influence its economic and social dynamics: the governmental area along HM Rafii Street and the commercial hub around Indrasari Market and Pangeran Antasari Street. This study aims to assess the relative dominance of each center in influencing their surrounding areas. A quantitative research approach was applied, combining literature review and comparative analysis to evaluate both central business districts (CBDs) using Gross Income Multiplier (GIM) and government-assessed property value (NJOP) as key indicators. The findings indicate that the Indrasari Market area currently holds a stronger economic influence. However, the HM Rafii area shows promising growth potential due to its strategic proximity to Iskandar Airport and Kumai Port. With the city’s continuing development, both centers are expected to play increasingly complementary roles, contributing to a balanced influence on Pangkalan Bun’s future urban and socio-economic landscape.